Muscle loss during primary debulking surgery and chemotherapy predicts poor survival in advanced‐stage ovarian cancer. Issue 2 (30th January 2020) - Huang, Chueh‐Yi; Yang, Yuh‐Cheng; Chen, Tze‐Chien; Chen, Jen‐Ruei; Chen, Yu‐Jen; Wu, Meng‐Hao; Jan, Ya‐Ting; Chang, Chih‐Long; Lee, Jie
Abstract: Background: Sarcopenia is commonly observed in patients with advanced‐stage epithelial ovarian cancer (EOC). However, the effect of body composition changes—during primary debulking surgery (PDS) and adjuvant platinum‐based chemotherapy—on outcomes of patients with advanced‐stage EOC is unknown. This study aimed to evaluate the association between body composition changes and outcomes of patients with stage III EOC treated with PDS and adjuvant platinum‐based chemotherapy. Methods: Pre‐treatment and post‐treatment computed tomography (CT) images of 139 patients with stage III EOC were analysed. All CT images were contrast‐enhanced scans and were acquired according to a standardized protocol. The skeletal muscle index (SMI), skeletal muscle radiodensity (SMD), and total adipose tissue index were measured using CT images obtained at the L3 vertebral level. Predictors of overall survival were identified using Cox regression models. Results: The median follow‐up was 37.9 months. The median duration between pre‐treatment and post‐treatment CT was 182 days (interquartile range: 161–225 days). Patients experienced an average SMI loss of 1.8%/180 days (95% confidence interval: −3.1 to −0.4; P = 0.01) and SMD loss of 1.7%/180 days (95% confidence interval: −3.3 to −0.03; P = 0.046). SMI and SMD changes were weakly correlated with body mass index changes (Spearman ρ for SMI, 0.15, P = 0.07; ρ for SMD, 0.02, P = 0.82). The modified Glasgow prognostic score was associated with SMI loss (odds ratio: 2.42, 95% confidence interval: 1.03–5.69; P = 0.04). The median time to disease recurrence was significantly shorter in patients with SMI loss ≥5% after treatment than in those with SMI loss <5% or gain (5.4 vs. 11.2 months, P = 0.01). Pre‐treatment SMI (1 cm 2 /m 2 decrease; hazard ratio: 1.08, 95% confidence interval: 1.03–1.11; P = 0.002) and SMI change (1%/180 days decrease; hazard ratio: 1.04, 95% confidence interval: 1.01–1.08; P = 0.002) were independently associated with poorer overall survival. SMD, body mass index, and total adipose tissue index at baseline and changes were not associated with overall survival. Conclusions: Skeletal muscle index decreased significantly during treatment and was independently associated with poor overall survival in patients with stage III EOC treated with PDS and adjuvant platinum‐based chemotherapy. The modified Glasgow prognostic score might be a predictor of SMI loss during treatment.